Kompetensi Guru Profesional Menurut Thahir Ibnu ‘Asyur dan Relevansinya dengan Kompetensi Guru Menurut Undang-Undang Nomor 14 Tahun 2005 Tentang Guru dan Dosen - Basith, Abdul; Mubin, Muhammad Ufuqul (EDU-RELIGIA : Jurnal Keagamaan dan Pembelajarannya, 2025)
This research aims to find 3 things; (1) The concept of Islamic education according to Ibn ‘Asyur; (2) Professional Teacher Competence according to Thahir Ibn ‘Asyur; (3) Relevance of the Competence of Professional Teachers according to Thahir Ibn 'Asyur with Teacher Competence according to Law Number 14 of 2005 concerning Teachers and Lecturers. This study uses a qualitative approach with the type of library research. Data collection techniques using documents related to the theme being studied. The results of the study show that; 1) The concept of education according to Thahir Ibn 'Assyria is 5; The concept of resource organization, the concept of al fitrah, the concept of al samahah, the concept of al Musawah and the concept of integration of educational aspects. 2) Teacher Competence according to Thahir 'Ibn 'Assyria is Professional Competence which contains the core points of pedagogical competence, personality competence, social competence, and professional competence itself. 3) There is a strong relevance to the competence of professional teachers according to Thahir Ibn 'Asyur with the competence of teachers according to Law Number 14 Article 10 Paragraph (1), Year 2005 concerning Teachers and Lecturers. So that the concept of Ibn 'Assyria is one of the main foundations for the development of teacher competence in the current modern era.